Analisis Metode SAW-WP-TOPSIS Dan Borda Count Pada Sistem Pendukung Keputusan Pemilihan Supervisor - Priyandini Pramithasari; Prisa Marga Kusumantara; Seftin Fitri Ana Wati (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2024)
A supervisor is a person who is responsible or has the authority to regulate the procedures for carrying out tasks in a company. The supervisor is the expert of all experts. Due to the important role of a supervisor, the selection of a supervisor must be appropriate, this can sometimes be a problem, if there are many candidates with the same abilities. To solve this problem, a Decision Support System (DSS) approach is used. The criteria used are: age, length of work, performance and absenteeism. This research uses 4 SPK methods, namely the SAW, WP, TOPSIS and borda count methods. Of the four methods, we will compare which method is more relevant for solving this problem using the Hamming Distance method. The results of this research show that the WP method is the most relevant method with the smallest percentage, namely, 47.15%, which means the WP method has the smallest level of nonconformity compared to the other 3 methods, namely SAW 56.81%, TOPSIS 82.95% and borda count 52.72%.